Combating workplace violence : creating and maintaining safe work environments - Nater, Felix P.; Van Fleet, David D.; Van Fleet, Ella W. (Emerald Publishing Limited : Information Age Publishing Inc., 2023)
"Today the threat of violence impacting worker safety and business operations is a major concern. It is crucial that thoughtful violence prevention policies and supporting violence response plans be developed before any incidents occur in order to properly prepare to use, respond, engage, and react appropriately. Once violence begins or ends is not good enough. The threats are real, and the risks must be managed. A violent threat from a current or former employee, domestic violence or relationship violence spillovers, and the threat posed by criminals committing crimes against people and property are concerns for which all organizations must prepare. Incident avoidance is not acceptable - indeed, most likely not possible. Our job is to make it manageable. The question is, "How prepared are you and your organization?" Instead of mounting costly legal defenses in the aftermath of a violent incident, organizations should develop defensible options that provide for a safe and secure workplace now and the avoidance of allegations of negligence in the future. Other factors affecting proper and appropriate decisions are the new legislation Section 5(a)(1) regarding the use of guns in the workplace and the Occupational Safety and Health Administration's intensified interest in citing employers who fail to resolve known hazards. Section 5(a)(1) of the Occupational Safety and Health Act (the "General Duty Clause") requires an employer to furnish its employees with "employment and a place of employment which are free from recognized hazards that are causing or are likely to cause death or serious physical harm to his employees." Employers who do not take steps to prevent or abate a recognized violence hazard in the workplace can be cited for failure to comply. This book, Combating Workplace Violence, provides a basic understanding of workplace violence as well as prevention policy and plan development in non-technical terms. The key to the successful development and implementation of a workplace prevention policy is the collaborative proactive leadership of company executives and management and the assistance of a qualified, reputable consultant. While the information and tools contained here are designed to serve as a baseline for any organization's solution to workplace violence, the material is useful to inform and educate any member of an organization. The unique framework (V-REEL℗ʼ) for analyzing the organization's internal environment to determine what can be done to try to eradicate or reduce workplace violence is especially useful. Ancillaries following each chapter provide additional information and tools to assist your planning. We envision this book being used to inform managers, human resource professionals, workers, and academics in all types of organizations. Hopefully, using the material and framework of this book, more organizations will develop policies, procedures, and practices to prevent workplace violence"--